Tasahul Imam Hakim: Case Study of Hadith 86 in the Book Mustadrok Al-Hakim - Faiz Abdullah; Tajul Arifin (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
In historical literature, there are many hadith scholars from various eras. These hadith scholars have different levels, especially in the science of al-jarh wa at-ta`dil. They can be classified as strict (mutasyaddid), moderate (mu`tadil), or lenient (mutasahhil). Among the scholars considered lenient is Imam Al-Hakim. This can be seen in his book Mustadrak al-Hakim. This paper uses a qualitative method, specifically a pure library research study, focusing on al-Mustadrak 'ala al-Shahihain as primary data, and applying the hadith science approach in analyzing the lenient perspective of Imam Al-Hakim. The result of this research is that the hadith discussed in this paper is considered weak (da'if) because in its chain of narrators (sanad) there are Qatadah bin Du'amah and Hasan al-Basri, both of whom are considered mudallis (obfuscators), and in this chain, neither of them narrated clearly (sarih).